Do Cortisol Levels Play a Role in Suicidal Behaviors and Non-Suicidal Self-Injuries in Children and Adolescents?—A Narrative Review - Bartłomiej Sporniak; Monika Szewczuk-Bogusławska (Brain Sciences)
Background/Objectives: Suicidal behaviors (SBs) and non-suicidal self-injury (NSSI) are significant mental health concerns in children and adolescents. The hypothalamic–pituitary–adrenal (HPA) axis, of which cortisol is a key hormone, has been implicated in these behaviors. This narrative review aims to explore whether cortisol levels play a role in SBs and NSSI in youth and to synthesize current evidence on this topic. Methods: A comprehensive literature search was conducted on studies published through November 2024, using PubMed, Web of Science, and Google Scholar databases. Studies were screened for eligibility, including only human studies published in English, with no animal models or studies excluding cortisol levels. A narrative synthesis approach was used due to the methodological diversity across studies. Due to limited adolescent-focused research, studies involving adults were also considered. Results: Findings indicate inconsistent cortisol patterns in relation to SBs and NSSI. Elevated cortisol levels are linked to SBs, with some studies suggesting they may predict future suicide attempts, though no definitive cause-and-effect relationship is established. Conversely, cortisol levels in relation to NSSI show mixed results, with some studies reporting no differences. Cortisol responses to stress, measured by saliva, blood, and hair, reveal complex interactions with psychological factors such as depression and impulsivity, influencing cortisol secretion. Discussion: Despite some evidence pointing to a role of cortisol dysregulation in SBs and NSSI, the relationship remains unclear due to study heterogeneity, including small sample sizes and methodological variations. Gender and the type of stressor used in studies also complicate the findings. Future research should prioritize longitudinal studies, better control for confounding factors, and utilize more diverse cortisol assessment methods to clarify these links. Conclusions: While cortisol may play a role in the pathophysiology of SBs and NSSI, further research is needed to establish clearer, more reliable patterns. Identifying alterations in cortisol levels may aid in early detection and targeted interventions for at-risk adolescents.